Collagen-fibril matrix properties modulate the kinetics of silica polycondensation to template and direct biomineralization. Issue 3 (28th January 2016) - Kahn, Jennifer L.; Eren, Necla Mine; Campanella, Osvaldo; Voytik-Harbin, Sherry L.; Rickus, Jenna L.
Abstract: Abstract : Fibrillar collagen networks template and direct biocompatible silica mineralization to produce hybrid materials for biomedical applications. Silica mineralization kinetics is critical for precision-tuning material properties, including mechanical strength, microstructure, and interface thickness. We investigated the effect of varying collagen template fibril volume fraction (0.2–0.8) and elasticity ( G ′ 200–1500 Pa) on silica mineralization rates. Measurement of the depletion of mono- and disilicic acids by silicomolybdic acid titration showed that silica condensation on collagen fibrils follows third-order kinetics. Resulting third-order rate constants increased linearly with storage modulus and quadratically with fibril volume fraction. A unique rheological approach used to probe the collagen template surface elasticity in real-time during silicification suggested a two-phase mechanism with high levels of surface-localized gelation in Phase 1 and high levels of bulk solution-localized gelation in Phase 2. These results provide a tool for controlling hybrid collagen-silica material properties by controlling local silica condensation rates.